Common goal - Reid, Rachel (Reid, Rachel. Game changers series, 2024)
Veteran goaltender Eric Bennett has faced down some of the toughest shooters on the ice, but nothing prepared him for his latest challenge--life after hockey. It's time to make some big changes, starting with finally dating men for the first time. Graduate student Kyle Swift moved to New York nursing a broken heart. He'd sworn to find someone his own age to crush on (for once). Until he meets a gorgeous, distinguished silver fox hockey player. Despite their intense physical attraction, Kyle has no intention of getting emotionally involved. He'll teach Eric a few tricks, have some mutually consensual fun, then walk away. Eric is more than happy to learn anything Kyle brings to the table. And Kyle never expected their friends-with-benefits arrangement to leave him wanting more. Happily-ever-after might be staring them in the face, but it won't happen if they're too stubborn to come clean about their feelings. Everything they both want is within reach... They just have to be brave enough to grab it.